Distribution and Biocontrol Potential of phlD+ Pseudomonads in Corn and Soybean Fields - McSpadden Gardener, Brian B.; Gutierrez, Laura J.; Joshi, Raghavendra; Edema, Richard; Lutton, Elizabeth (Biological Control, 2005)
The abundance and diversity of phlD+ Pseudomonas spp. colonizing the rhizospheres of young, field-grown corn and soybean plants were assayed over a 3-year period. Populations of these bacteria were detected on the large majority of plants sampled in the state of Ohio, but colonization was greater on corn. Although significant variation in the incidence of rhizosphere colonization was observed from site to site and year to year on both crops, the magnitude of the variation was greatest for soybean. The D genotype was detected on plants collected from all 15 counties examined, and it represented the most abundant subpopulation on both crops. Additionally, six other genotypes (A, C, F, I, R, and S) were found to predominate in the rhizosphere of some plants. The most frequently observed of these were the A genotype and a newly discovered S genotype, both of which were found on corn and soybean roots obtained from multiple locations. Multiple isolates of the most abundant genotypes were recovered and characterized. The S genotype was found to be phylogenetically and phenotypically similar to the D genotype. In addition, the novel R genotype was found to be most similar to the A genotype. All of the isolates displayed significant capacities to inhibit the growth of an oomycete pathogen in vitro, but such phenotypes were highly dependent on media used. When tested against multiple oomycete pathogens isolated from soybean, the A genotype was significantly more inhibitory than the D genotype when incubated on 1/10× tryptic soy agar and 1/5× corn meal agar. Seed inoculation with different isolates of the A, D, and S genotypes indicated that significant root colonization, generally in excess of log 5 cells per gram of root, could be attained on both crops. Field trials of the A genotype isolate Wayne1R indicated the capacity of inoculant populations to supplement the activities of native populations so as to increase soybean stands and yields. The relevance of these findings to natural and augmentative biocontrol of root pathogens by these bacteria is discussed.
Keywords: Biogeography; DAPG